APPLICATION OF PROBLEM BASED LEARNING INTEGRATED WITH TEACHING AT THE RIGHT LEVEL TO IMPROVE IPAS LEARNING OUTCOMES - Rifalni Saeful Pratiwi; Nivelia Triyani; Mega Lestari Br Sinuraya; Nur Azizah Afwanda; Herliani Izhar; Fitri Siti Sundari; Siti Nurjanah (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
The study purposes to improve students' learning results in the subject of Natural and Social Sciences (IPAS) by applying the Problem Based Learning (PBL) model integrated with the Teaching at The Right Level (TaRL) approach. The background of this study is the low learning outcomes in IPAS at SDN Bondongan due to teacher-centered learning that does not consider the different learning abilities of students. This investigation is a Classroom Action Research (CAR) conducted in two cycles, involving 27 fifth-grade students in the even semester of the 2024/2025 academic year. Tests of learning outcomes and observations of students' educational activities were used to gather data. The average scores and the proportion of students who learned everything they needed to from cycle I to cycle II both significantly improved, according to the results. The classical completeness rose from 33.33% to 88.89%, while the average score rose from 50 to 80. In addition, the active participation and engagement of students in learning have also increased. This finding shows that the application of the PBL model combined with the TaRL approach is effective in improving IPAS learning results .